Strategies for the Prevention of Violence in Institutional Care: A Qualitative Interview Study With Ward Managers - Lindow, Martin; Kjellin, Lars; Engström, Ingemar; Pelto-Piri, Veikko (Frontiers in Psychiatry, 2022)
Background: The presence of violence within psychiatric and residential settings remains a challenge. Research on this problem has often focused on describing violence prevention strategies from either staffs’ or service users’ perspectives, and the views of ward managers has been largely overlooked. The aim of the present study was therefore to identify ward managers’ strategies to prevent violence in institutional care, focusing on safety and values. Methods: Data were collected using semi-structured interviews with 12 ward managers who headed four different types of psychiatric wards and two special residential homes for adolescents. Qualitative content analysis was applied, first using a deductive approach, in which quotes were selected within a frame of primary, secondary, and tertiary prevention, then by coding using an inductive approach to create themes and subthemes. Results: Ward managers’ strategies were divided into the four following themes: 1) Balancing being an active manager with relying on staff’s abilities to carry out their work properly while staying mostly in the background; 2) Promoting value awareness and non-coercive practices in encounters with service users by promoting key values and adopting de-escalation techniques, as well as focusing on staff-service user relationships; 3) Acknowledging and strengthening staff’s abilities and competence by viewing and treating staff as a critical resource for good care; and 4) Providing information and support to staff by exchanging information and debriefing them after violent incidents. Conclusions: Ward managers described ethical challenges surrounding violence and coercive measures. These were often described as practical problems, so there seems to be a need for a development of higher ethical awareness based on a common understanding regarding central ethical values to be respected in coercive care. The ward managers seem to have a high awareness of de-escalation and the work with secondary prevention, however, there is a need to develop the work with primary and tertiary prevention. The service user group or user organizations were not considered as resources in violence prevention, so there is a need to ensure that all stakeholders are active in the process of creating violence prevention strategies.